Analysis of Systemic Sclerosis-associated Genes in a Turkish Population - DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2016)
Objective. To evaluate the genetic background of systemic sclerosis ( SSc) in the Turkish population. Methods. There were 354 cases and 718 unaffected controls from Turkey genotyped for the most relevant SSc genetic markers ( IRF5-rs10488631, STAT4-rs3821236, CD247-rs2056626, DNASE1L3-rs35677470, IL12A-rs77583790, and ATG5-rs9373839). Association tests were conducted to identify possible associations. Results. Except for ATG5, all the analyzed genes showed either significant associations ( IRF5: p = 1.32E-05, OR 1.76; CD247: p = 2.20E-03, OR 0.75) or trends of association ( STAT4: p = 0.066, OR 1.21; IL12A: p = 0.079, OR 4.07; DNASE1L3: p = 0.097, OR 1.41) with the overall disease or with specific phenotypes. Conclusion. The genetic component of SSc seems to be similar between Turks and Europeans.
Keywords: SYSTEMIC SCLEROSIS; GENETICS; TURKEY; 2013 CLASSIFICATION CRITERIA; RHEUMATOLOGY/EUROPEAN LEAGUE; SUSCEPTIBILITY LOCI; AMERICAN-COLLEGE; SCLERODERMA; GENETICS; DISEASE